Birthplace, Religion, and Agricultural Productivity in Peterborough County, 1851 and 1861 - Parkinson, Marshall Grenville (My University, 1988)
The influence of birthplace and religion on rural settlement in mid-nineteenth century southern Ontario is investigated. Over 1,000 settlers at each of the 1851 and 1861 Canada census dates who were born in either England, Ireland or Scotland and who were either Catholic, Anglican. Presbyterian or Methodist are of interest.
Mean crop productivity and land improvement measures are determined for each nativity, religious, and combined cultural characteristic group. Average cash value of farm (land and buildings) in 1861 is similarly examined. The proximity of each settler with a particular combination of nativity and religion to the nearestneighbour sharing the same set of cultural characteristics is measured. Finally, the influence of soil quality on crop productivity, land improvement, and farm value is examined. Changes of propinquity. crop productivity. and land improvement from 1851 to 1861 are also investigated.
The Irish Catholics were the most clustered and the Irish Protestants were the most dispersed at each census date. The Scottish were the most productive and the Irish were the least productive in both 1851 and 1861. The Presbyterians were the best producers in the religious category, while the Catholics were at the lower end of the scale. Land improvement results were similar with the Scottish. Presbyterians, and Scottish Presbyterians at or close to the top of the list and the Irish, Catholics, and Irish Catholics at or close to the bottom. The same pattern is evident in the comparison of farm values.
A clear profile emerges of the Scottish Presbyterian as generally the most productive and most industrious settler who operated the most valuable farm. At the other end of the scale the Irish Catholic generally was the lowest producer, had the least amount of land cleared and farmed the least valuable property.
[missing page 130]
Keywords: Geography; Geography